Title: race and ethnicity and the risk of community-acquired third-generation cephalosporin-resistant uropathogens: a systematic review and meta-analysis - Sweta Balaji; Sarah Blackmon; Esther E. Avendano; Samson Alemu Argaw; Rebecca A. Morin; Nanguneri Nirmala; Shira Doron; Maya L. Nadimpalli (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract